Barriers and enablers to bowel cancer screening participation in remote Tasmania: A qualitative study using the theoretical domains framework - Gadd, Nicola; Lee, Simone; Hughes, Jessica; Sharman, Matthew J.; Hoang, Ha; Obamiro, Kehinde (The Australian journal of rural health, 2024)
Objective Identify barriers and enablers for remote Tasmanians participating in bowel cancer screening through the National Bowel Cancer Screening Program. Setting A small remote Tasmanian community. Participants Tasmanian remote community members aged 50 years and over. Design A qualitative study conducted 16 semi‐structured interviews. Two researchers conducted in‐person and telephone interviews. Questions were directed by an interview guide developed using the Theoretical Domains Framework for behaviour change and Behaviour Change Wheel. Two researchers analysed data using directed content analysis with a flexible inductive approach. Results Four themes related to barriers and enablers to completing the National Bowel Cancer Screening Program screening kit in remote Tasmania. Themes included the subject of screening, physical screening kit, the process and outcome of the kit. Several barrier and enabler sub‐themes overlapped or were linked, as many enablers mitigated barriers. For example, social influences, awareness level, steps in completing screening, and planning and timing to screen. Social support and discussing screening with others were key enablers, whereas lack of these were barriers. For remote communities, taking the kit to the post office was a barrier from often knowing the post officer. A bowel bus providing screening and information support services may reduce the travel burden of follow‐up diagnostic tests and support low‐literacy individuals to screen. Conclusion Barriers and enablers exist within each stage of the screening process, from what influences an individual decision to screen, through to the outcome. To improve screening rates in rural/remote Tasmania, barriers and enablers to screening must be considered.